2022
DOI: 10.3390/insects13010054
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Trees Infested by the Invasive Primary Wood-Borer Aromia bungii (Coleoptera: Cerambycidae)

Abstract: The expanding distribution and tree damage of the invasive, primary wood-borer Aromia bungii (Coleoptera: Cerambycidae), which kills trees of the Rosaceae family, is a problem in intruded areas. However, the tree characteristics associated with infestation by A. bungii, which are useful for early detection or prioritizing preventive measures, are not well examined. We investigated the presence or absence of tree damage (response variable) in pre- and post- surveys along with tree characteristics (four explanat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Accordingly, several studies on bark‐ and wood‐boring insects have also reported that infested trees are usually larger, as large trees can provide more food sources (Ferrenberg, 2016; Korolyova et al., 2022). Furthermore, there are reports on the positive effects of tree size on the landing rate of adults (Yamamoto et al., 2022). As tree height exhibited only a weak effect in the present study, X. ceramica is mostly attracted to thicker trees with vigorous secondary growth that provide more food from inner bark tissue and sapwood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, several studies on bark‐ and wood‐boring insects have also reported that infested trees are usually larger, as large trees can provide more food sources (Ferrenberg, 2016; Korolyova et al., 2022). Furthermore, there are reports on the positive effects of tree size on the landing rate of adults (Yamamoto et al., 2022). As tree height exhibited only a weak effect in the present study, X. ceramica is mostly attracted to thicker trees with vigorous secondary growth that provide more food from inner bark tissue and sapwood.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to prevent and minimize losses from pest infestations, detailed knowledge of the bionomy and habitat requirements of pests is crucial for adopting specific silvicultural and technical control measures at different stages of forest rotation. In relation to the ecological requirements of bark‐ and wood‐boring insects, previous studies of various species have reported that information concerning tree and stand characteristics related to infestation, such as tree size (Nelson et al., 2017; Suksavate et al., 2021), tree vitality (Hlásny et al., 2021; Kašák & Foit, 2018), bark roughness (Ferrenberg & Mitton, 2014; Yamamoto et al., 2022), microclimate (Holuša et al., 2021), understorey gradient (Cizek & Vodka, 2013), stand edge/interior ratio (Majdák et al., 2021), stand age, density and species composition (Marini et al., 2022; Sproull et al., 2015), is essential. Moreover, studies have reported the characteristics of host trees susceptible to infestation by several cossid species; for example, Cossus cossus (Linnaeus, 1758) was found to prefer to attack larger, more damaged and more stressed trees with cracked bark (Kaplan & Turanlı, 2018; Turundaevskaya, 1992).…”
Section: Introductionmentioning
confidence: 99%